Binding Force of International Agreements: Perspectives of International Law and National Law - Pitaloka, Diva; Putri, Yunita Maya; Becánics, Adrienn; Ernawati, Ninin (Journal of Law and Policy Transformation, 2025)
International treaties are one of the main sources of international law that have binding power for the parties that agree to them. In the context of relations between countries, international treaties are an important instrument in regulating various common interests, ranging from trade issues, the environment, to human rights. This article examines the binding power of an international treaty from two perspectives: international law and national law. From an international law perspective, a treaty becomes binding after being ratified by the parties according to the principle of pacta sunt servanda stipulated in the 1969 Vienna Convention on the Law of Treaties. Meanwhile, from a national law perspective, the recognition and application of international treaties depend on the domestic legal system of each country, whether it adheres to the principle of monism or dualism. This study also highlights the challenges of implementing international treaties in Indonesia, including the ratification mechanism and the role of legislative institutions. Through a normative approach and case studies, this article aims to provide a comprehensive understanding of the dynamics of the binding power of international treaties within the framework of global and national law.